EFFECT OF CRICKET FLOUR (Gryllus mitratus Burm) ON BROILER ABDOMEN FAT DISTRIBUTION - M. F. R., Ramadhan,; Astawa, I P. A.; Wibawa, A.A.P.P. (Jurnal Peternakan Tropika; Vol 12 No 5 (2024): Vol. 12 No. 5 Tahun 2024; September - October, 2024)
This study aims to determine the effect of using cricket flour (Gryllus mitratus Burm) on the distribution of abdominal fat in broilers. The design used was a completely randomized design consisting of four treatments and four replications, each replication consisting of four broilers. Treatment consisted of P0 (ration without replacement with cricket flour), P1 (2% commercial ration replaced with 2% cricket flour), P2 (4% commercial ration replaced with 4% cricket flour), P3 (6% commercial ration replaced with 6 % cricket flour). The variables observed were slaughter weight, pad fat, mesenteric fat, ventricular fat, and abdominal fat. The results of the research showed that broiler slaughter weight in the 2% cricket flour (P1), 4% cricket flour (P2), and 6% cricket flour (P3) treatment had a significantly higher effect (P<0.05) compared to the P0 treatment. The percentage of pad fat, percentage of mesenteric fat, percentage of ventricular fat, and percentage of abdominal fat in treatments P1, P2, and P3 were significantly lower (P<0.05) compared to treatment P0. The results of this research can be concluded that the use of 2%, 4%, and 6% cricket flour in commercial rations can increase slaughter weight and reduce the percentage of pad fat, mesenteric fat percentage, ventricular fat percentage, and abdominal fat percentage.